KESTABILAN MODEL POPULASI MANGSA PEMANGSA DENGAN LAJU PEMANENAN TETAP - Tri Hidayati (Delta: Jurnal Ilmiah Pendidikan Matematika, 2018)
The aim of this research is to analyze predator- prey population model with constant rate of harvesting which is called The Lotka Volterra model of predator-prey and to determine the stability from equilibrium points. This research used literature study, it means that the resources for creating this research are taken, collected, and arranged from various existed research result and books. The procedural steps in this research namely looking for the equilibrium from each equation then analyzing the behavior of equilibrium points obtained. In this research, pre and predator population model was analyzed, that has equilibrium point , and . The equilibrium of predator-prey and was reached in equilibrium point . The constant rate of harvesting in predator-prey population caused the equilibrium point had been changed, that was for obtaining the equilibrium point x by finding the roots of polynomial        and for equilibrium point y is obtained by substitution x value that found to .